2018
DOI: 10.1016/j.ajog.2018.04.050
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal skeletal muscle activity precedes spontaneous menstrual cramping pain in primary dysmenorrhea

Abstract: Abdominal muscle activity may contribute to cramping pain in primary dysmenorrhea but is resolvable with naproxen. Dysmenorrheic patients without cramp-associated abdominal muscle activity exhibit widespread pain sensitivity (lower pressure pain thresholds) and are more likely to also have a chronic pain diagnosis, suggesting their cramps are linked to changes in central pain processes. This preliminary study suggests new tools to phenotype menstrual pain and supports the hypothesis that multiple distinct mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…However, a major limitation of existing research is that it remains unclear whether enhanced pain sensitivity develops as a function of repeated episodes of pain or whether these differences in girls with PD may reflect a more stable, central sensitization to pain. Ongoing research has begun to identify genetic [11; 48], physiological [28], and symptom-based phenotypes [6] in women with PD; however, further research in this area is warranted, particularly with adolescents within the first 2-3 yeas of starting menstruation, to clearly determine how, when, and for whom these alterations develop.…”
Section: Discussionmentioning
confidence: 99%
“…However, a major limitation of existing research is that it remains unclear whether enhanced pain sensitivity develops as a function of repeated episodes of pain or whether these differences in girls with PD may reflect a more stable, central sensitization to pain. Ongoing research has begun to identify genetic [11; 48], physiological [28], and symptom-based phenotypes [6] in women with PD; however, further research in this area is warranted, particularly with adolescents within the first 2-3 yeas of starting menstruation, to clearly determine how, when, and for whom these alterations develop.…”
Section: Discussionmentioning
confidence: 99%
“…Participants included in this study were enrolled between March 2015 and November 2017. Some participant data from the MRI and ultrasound study has already been published 6, 7 . The method in this paper was used in those prior studies 6, 7 to investigate the role of uterine contractions and abdominal muscle activity in menstrual pain.…”
Section: Methodsmentioning
confidence: 99%
“…To validate a new metric for evaluating spontaneous pain and its temporal characteristics, we investigated women with menstrual period pain, clinically known as dysmenorrhea. Previously, a hand‐held squeeze bulb was used to characterize the temporal relationship between cramping pain and uterine activity with magnetic resonance imaging (MRI) 6 or abdominal muscle activity with Electromyography, 7 however, this method to measure pain intensity was not validated. We tested the hypothesis that worse global self‐reported rating of menstrual cramping pain is associated with more prolonged, intense, and frequent bulb squeezing pain bouts in women with dysmenorrhea.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors argued that PD may contribute to the development of a chronic pelvic pain disorder [1,2], showing high comorbidity with other chronic pain conditions, such as irritable bowel syndrome, migraines and fibromyalgia [10]. Nevertheless, since only 75%-80% of women treated with pharmacology experienced relief from PD symptoms, it is suggested that the nociceptive mechanisms underlying PD are not yet understood [11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Blakey et al [14] assume that PD can be caused by a dyssynergy between the muscles of the pelvic cavity and the soft tissues. Some treatments proposed to manage PD, such as heat, massage, Transcutaneous electrical nerve stimulation (TENS) or vertebral manipulations, could plausibly address the dysfunction of the abdominal muscles [11,15,16]. Nevertheless, few research studies have been conducted establishing associations between the abdominal muscles and PD.…”
Section: Introductionmentioning
confidence: 99%